ANALISIS PENANGANAN PIUTANG BERMASALAH PADA PT CSUL FINANCE CABANG PALEMBANG - Tedy Setiawan Saputra (Jurnal Ilmiah Ekonomi Global Masa Kini)
The indicator of the finance company growth is the increase of the total asset and low of the nonperforming financing.  The nonperforming financing of the PT CSUL Finance Palembang Branch has been increasing in 2017 about 48.31%.  The research aims to know how the company maintaining the nonperforming financing.  The research utilizes the quantitative descriptive method.  The research result showed that management of the nonperforming finance in PT CSUL Finance, Palembang Branch, is not good enough,and the company must be give a special attention for the account receivable which overdue more than 180 days.  This condition has been caused by an unbalanced between the total manpower of the collection division and the total account should be handling, and also caused by a wide covering collection area.  The writer recommended to the company to recruiting a new collection staff and limitation of the coverage area as well.Keyword: Non performing Financing, Man power, Coverage area